2015
DOI: 10.1055/s-0035-1545842
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Properties of the Leaf Essential Oil of Zornia brasiliensis

Abstract: Zornia brasiliensis, popularly known as "urinária", "urinana", and "carrapicho", is a medicinal plant used in Brazilian northeast folk medicine as a diuretic and against venereal diseases. The aim of this study was to investigate the chemical composition and antitumor potential of the leaf essential oil of Z. brasiliensis. The essential oil was obtained by hydrodistillation using a Clevenger-type apparatus and analyzed by GC-MS and GC-FID. Its composition was characterized by the presence of trans-nerolidol, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
(21 reference statements)
0
28
0
2
Order By: Relevance
“…Table presents the results found. Our pre‐clinical anticancer drug screening programme, which is based in the United States National Cancer Institute programme, demonstrated that extracts/oils with IC 50 values below 30 μg/mL and pure compounds with IC 50 values below 4 μg/mL in tumour cell line assays are promising . Therefore, the EO obtained of A. vepretorum leaf presents promising results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table presents the results found. Our pre‐clinical anticancer drug screening programme, which is based in the United States National Cancer Institute programme, demonstrated that extracts/oils with IC 50 values below 30 μg/mL and pure compounds with IC 50 values below 4 μg/mL in tumour cell line assays are promising . Therefore, the EO obtained of A. vepretorum leaf presents promising results.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic toxicological effects were investigated as previously described . Mice were weighed at the beginning and end of the experiment.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Several anticancer drugs, such as vincristine, etoposide, vinblastine, irinotecan, paclitaxel (taxol) and topotecan are botanical secondary metabolites or semi-synthetic derivatives ( 1 ). Apigenin ( 2 ), deguelin ( 3 ), kaempferol ( 4 ), luteolin ( 5 7 ), quercetin ( 8 11 ), rutin ( 12 16 ), tricin ( 17 ), xanthomicrol ( 18 ), α-copaene ( 19 ), α-humulene ( 20 , 21 ) and β-himachalene ( 22 ) are some botanical ingedients that have been investigated as possible future remedies for use in chemotherapy. Xanthomicrol and calycopterin have also been shown to exert potent inhibitory effects on microvessel outgrowth and that these anti-angiogenic effects enhance the antitumor activity ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…é utilizada para o tratamento de disenteria e doenças venéreas na Índia (Arunkumar et al 2014). No Brasil, Z. brasiliensis é comumente usada como diurética (Costa et al 2015). Vários estudos identificaram ainda propriedades moluscicidas (Kloos et al 1987), antiespasmódica (Rojas et al 1999), antibiótica (Obi et al 2007;Arunkumar et al 2014), antitumoral (Arunkumar et al 2012;Costa et al 2015), antinociceptiva (Silva et al 2013) e antifúngica (Arunkumar et al 2014) em diferentes espécies de Zornia.…”
Section: Introductionunclassified